On One Sufficient Condition for the Validity of the Strong Law of Large Numbers for Martingales - Koval, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove a theorem on the strong law of large numbers for martingales. The existence of higher moments is not assumed. From the theorem proved, we deduce numerous well-known results on the strong law of large numbers both for martingales and for sequences of sums of independent random variables.